CSR activities of a hospital: perspectives of stakeholders. (2018) - Tripathi, Nachiketa; Bharadwaja, Manaswita; Ghosh, Vinit; Kataki, Bidyut Bikash
The present research investigates the gaps between CSR projections of a hospital and stakeholder's perceptions about these CSR activities by analysing multi-source data of stakeholders. Two sets of studies were conducted, namely, study A (quantitative) and study B (qualitative). Study A was based on survey method which assessed the perceptions of stakeholders, namely, community (N = 100), customers (N = 75) and employees (N = 40). An equivalent Assamese version of the questionnaire was constructed for the convenience of the local population. Study B used interview method to evaluate the CSR projections of the hospital. Data for study B were collected from the top management of the hospital using key informant approach. Both the quantitative and qualitative sets of data were analysed individually and results of qualitative study were used to augment the results of quantitative study. The findings suggest that gaps exist between the hospital's CSR projections and perceptions of local community, whereas the perceptions of customers and employees converge with hospital's claims.